A review of knowledge gaps and tools for orbivirus research - Drolet, Barbara S.; Van Rijn, Piet; Howerth, Elizabeth W.; Beer, Martin; Mertens, Peter P. (Mary Ann Liebert, Inc, 2015)
Although recognized as causing emerging and re-emerging disease outbreaks worldwide since the late 1800s, there has been growing interest in the United States and Europe in recent years in orbiviruses, their insect vectors, and the diseases they cause in domestic livestock and wildlife. This is due, in part, to the emergence of bluetongue (BT) in northern Europe in 2006–2007 resulting in a devastating outbreak, as well as severe BT outbreaks in sheep and epizootic hemorrhagic disease (EHD) outbreaks in deer and cattle in the United States. Of notable concern is the isolation of as many as 10 new BT virus (BTV) serotypes in the United States since 1999 and their associated unknowns, such as route of introduction, virulence to mammals, and indigenous competent vectors. This review, based on a gap analysis workshop composed of international experts on orbiviruses conducted in 2013, gives a global perspective of current basic virological understanding of orbiviruses, with particular attention to BTV and the closely related epizootic hemorrhagic disease virus (EHDV), and identifies a multitude of basic virology research gaps, critical for predicting and preventing outbreaks
Keywords: Orbivirus; Bluetongue virus; Epizootic hemorrhagic disease virus; Culicoides; Midges; Review